2005
DOI: 10.7863/jum.2005.24.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Diagnosis of Plantar Vein Thrombosis

Abstract: Objective. The purpose of this series is to describe sonographic findings in 3 patients with plantar vein thrombosis. Methods. Three patients had sudden pain and swelling at the plantar side of the affected foot. Sonography of the plantar foot was performed with a broadband linear array working at 5 to 12 MHz. Gadolinium-enhanced magnetic resonance imaging was performed in 1 patient. Results. Sonography showed enlarged incompressible plantar veins in all 3 cases. Magnetic resonance imaging confirmed venous thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 5 publications
0
38
0
2
Order By: Relevance
“…During our analysis, we found a few isolated case reports (5)(6)(7) and others with a larger number of cases described by Bernathova et al (2) and Barros and Labropoulos (8) . Therefore, we believe that this article presents the largest series reported in the English-language literature.…”
Section: Discussionmentioning
confidence: 91%
“…During our analysis, we found a few isolated case reports (5)(6)(7) and others with a larger number of cases described by Bernathova et al (2) and Barros and Labropoulos (8) . Therefore, we believe that this article presents the largest series reported in the English-language literature.…”
Section: Discussionmentioning
confidence: 91%
“…[2][3][4] Review of the literature showed that plantar vein thrombosis has been associated with athletic activity, 2 with immobilization following surgery, 5,6 with the coagulation disorders anticardiolipin antibody syndrome 4 and prothrombin G20210A mutation, 3 and as a paraneoplastic syndrome in a patient with bone metastasis. 2 We here present the first case of plantar vein thrombosis without prior surgery, malignancy, or coagulation disorders. In our case, plantar vein thrombosis was most probably caused by a busy night duty on ICU followed by a prolonged sleeping period for 14 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Despite, the exact etiology of plantar vein thrombosis still being unknown, the predisposing conditions include previous trauma or surgery, paraneoplastic conditions, and coagulation disorders. [2][3][4] Indicative symptoms often imply swelling and pain of the respective foot. We present the first case of isolated plantar vein thrombosis independent of trauma, surgery, or malignant disease, most probably caused by a busy night duty on the intensive care unit (ICU) followed by a prolonged sleeping period.…”
mentioning
confidence: 99%
“…Die häufigsten Symptome der Plantarvenenthrombose sind Fußschmerzen und eine Schwellung (2,3,11). Die Rezidivraten lagen in der Studie von Czihal bei 27 % (2).…”
unclassified
“…Das Fuß-MRT wird nicht selten zur Differenzialdiagnostik bei Fußschmerzen durchgeführt und kann auch eine Plantarvenenthrombose, bei einem Füllungsdefekt der Vene, nachweisen (6,11 (8).…”
unclassified